EFFECTS OF EMPLOYEE MOTIVATION ON ORGANIZATIONAL PERFORMANCE AT ETHIOPIAN TELECOM SOUTH WEST REGION JIMMA - Wolde Shiferaw; Shimkit Kelkay; Emnet Negash; Aregu Asmare (Integrated Journal of Business and Economics (IJBE), 2020)
The study examined the effects of employee motivation on organization performance of crews in Ethio telecom South West Region Jimma. The data were collected through self-administered questionnaire from 229 respondents and 219 were returned.  Both primary and secondary sources of data were consumed in this study. The quantitative research approach was implemented and simple random sampling technics were adopted to provide equal chances for respondents. The data were analyzed by SPSS version 20.0 using an exploratory research design and data was analyzed using correlation and regression analysis. The correlation analysis indicates that there was a positive relationship between the independent variables (employee motivation) and dependent variables (organization performance). The result of the regression implies that the independent variables (employee benefit, promotion, teamwork, training and working environment) have accounted for 78.1% of variance in the dependent variable. Based on the outcome of the study, the researchers recommend that, it is better if the company focuses on employee motivation factors, mostly Promotion, employee benefit, teamwork and training so as to improve its performance. Based on the outcome of the study, the researchers recommend that, it is better if the company focuses on employee motivation factors, mostly Promotion, employee benefit, teamwork and training improve its performance.